From knowledge to action: How nutrition knowledge shapes sustainable eating and Mediterranean diet adherence - Öngün Yilmaz, Hande; Arslan, Sedat; Tari Selçuk, Kevser; Bayram, Hatice Merve; Ozturkcan, Arda (Frontiers in Nutrition, 2025)
BackgroundThe aim of this study was to examine the effects of nutrition knowledge on sustainable and healthy eating behaviours and adherence to the Mediterranean diet in adults.MethodsThis cross-sectional study analysed data from 1712 participants aged 18–64 years living in Türkiye who participated in an online survey. Data were collected using the Descriptive Information Form, the Nutrition Knowledge Scale (NKS), the Sustainable and Healthy Eating Behaviours Scale (SHE), and the Mediterranean Diet Adherence Scale (MEDAS).ResultsThe mean score of the adults with a mean age of 30.69 ± 10.89 years was 82.70 ± 15.81 and 28.2% had a high level of nutrition knowledge. Multivariate linear regression analysis showed that after controlling for socio-demographic factors, the increase in nutritional knowledge level was associated with an increase in the components of sustainable and healthy dietary eating behaviours Quality labels (β: 0.100, p < 0.05), Seasonal food and avoiding food waste (β: 0.134, p < 0.05), Animal welfare (β: 0.031, p < 0.05), Healthy and Balanced Diet (β: 0.193, p < 0.05) and Low fat (β: 0.130, p < 0.05) and Mediterranean diet compliance (β: 0.185, p < 0.001) as predictors of adherence to the Mediterranean diet.ConclusionThe results of the study revealed that increasing the level of nutritional knowledge plays a key role not only for individual health but also for the sustainability of our planet. In this context, programmes that enhance nutritional knowledge are key to promoting sustainable, healthy eating and adherence to the Mediterranean diet.